The class of b-limited operators - El Kaddouri Abdelmonaim (Acta scientiarum mathematicarum, 2016)
We introduce a new class of operators that we call b-limited operators. Properties of b-limited operators, the relationship between the b-limited operators and various classes of operators are studied.